How quality improvement collaboratives work to improve healthcare in care homes: a realist evaluation. (16th February 2021) - Devi, Reena; Chadborn, Neil H; Meyer, Julienne; Banerjee, Jay; Goodman, Claire; Dening, Tom; Gladman, John R F; Hinsliff-Smith, Kathryn; Long, Annabelle; Usman, Adeela; Housley, Gemma; Lewis, Sarah; et al.
Abstract: Background: Quality improvement collaboratives (QICs) bring together multidisciplinary teams in a structured process to improve care quality. How QICs can be used to support healthcare improvement in care homes is not fully understood. Methods: A realist evaluation to develop and test a programme theory of how QICs work to improve healthcare in care homes. A multiple case study design considered implementation across 4 sites and 29 care homes. Observations, interviews and focus groups captured contexts and mechanisms operating within QICs. Data analysis classified emerging themes using context-mechanism-outcome configurations to explain how NHS and care home staff work together to design and implement improvement. Results: QICs will be able to implement and iterate improvements in care homes where they have a broad and easily understandable remit; recruit staff with established partnership working between the NHS and care homes; use strategies to build relationships and minimise hierarchy; protect and pay for staff time; enable staff to implement improvements aligned with existing work; help members develop plans in manageable chunks through QI coaching; encourage QIC members to recruit multidisciplinary support through existing networks; facilitate meetings in care homes and use shared learning events to build multidisciplinary interventions stepwise. Teams did not use measurement for change, citing difficulties integrating this into pre-existing and QI-related workload. Conclusions: These findings outline what needs to be in place for health and social care staff to work together to effect change. Further research needs to consider ways to work alongside staff to incorporate measurement for change intoQI.